Dynamics of Antibody and T Cell Immunity against SARS-CoV-2 Variants of Concern and the Impact of Booster Vaccinations in Previously Infected and Infection-Naïve Individuals - Michel R. Faas; Willem A. Mak; Hilde Y. Markus; Ellen M. van der Zwan; Marijke van der Vliet; Johannes G. M. Koeleman; David S. Y. Ong (Vaccines, 2022)
Despite previous coronavirus disease 2019 (COVID-19) vaccinations and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, SARS-CoV-2 still causes a substantial number of infections due to the waning of immunity and the emergence of new variants. Here, we assessed the SARS-CoV-2 spike subunit 1 (S1)-specific T cell responses, anti-SARS-CoV-2 receptor-binding domain (RBD) IgG serum concentrations, and the neutralizing activity of serum antibodies before and one, four, and seven months after the BNT162b2 or mRNA-1273 booster vaccination in a cohort of previously infected and infection-naïve healthcare workers (HCWs). Additionally, we assessed T cell responses against the spike protein of the SARS-CoV-2 Delta, Omicron BA.1 and BA.2 variants of concern (VOC). We found that S1-specific T cell responses, anti-RBD IgG concentrations, and neutralizing activity significantly increased one month after booster vaccination. Four months after booster vaccination, T cell and antibody responses significantly decreased but levels remained steady thereafter until seven months after booster vaccination. After a similar number of vaccinations, previously infected individuals had significantly higher S1-specific T cell, anti-RBD IgG, and neutralizing IgG responses than infection-naïve HCWs. Strikingly, we observed overall cross-reactive T cell responses against different SARS-CoV-2 VOC in both previously infected and infection-naïve HCWs. In summary, COVID-19 booster vaccinations induce strong T cell and neutralizing antibody responses and the presence of T cell responses against SARS-CoV-2 VOC suggest that vaccine-induced T cell immunity offers cross-reactive protection against different VOC.